Najnowsze rosyjskie parafrazy "Zdrowaś Mario" - Prus, Kazimierz (Rusycystyczne Studia Literaturoznawcze, 2016)
Ave Maria is a universal Marian prayer. It is very popular in Russia, which is undoubtedly connected with the significance of Marian devotions in this country. In the most recent Internet prayer, it is widely paraphrased, transformed, included in other original poems, and textually modified. Frequently, the intertextual links point to its particular lines and images. Only in one translation discussed, Ave Maria is deprived of its mode of prayer and supplemented with a satanist tone. The intertextual variants of Ave Maria this paper confronts confirm the capacity of the source text, which results in the new ways of articulation in Russian language.